2020
DOI: 10.3390/agriculture10100447
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Management Strategies of Plant Parasitic Nematodes in Moroccan Organic Farming and Their Relationship with Soil Physico-Chemical Properties

Abstract: Organic farming has been increasing steadily over the last decade and is expected to grow drastically in the future. Plant parasitic nematodes (PPNs) are known as one of the most important pests attacking various plants in conventional and organic farming systems. A survey was conducted in January 2019 to determine the occurrence and diversity of PPNs, their associations with soil properties, and to assess their management methods in organically farmed fields in Southern Morocco. Twelve genera of PPNs were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…It was shown that soil texture (mainly sandy and clay content) affected nematode occurrence. A recent study conducted by Krif et al [80] reported that many PPNs populations were strongly correlated with soil clay, sand, and silt content in vegetable crops, while Van Diepeningen et al [81] demonstrated the same effect in both conventional and organic agricultural settings, and they found a prominent impact. In addition, this correlation could strongly define PPNs population structures [82,83].…”
Section: Discussionmentioning
confidence: 98%
“…It was shown that soil texture (mainly sandy and clay content) affected nematode occurrence. A recent study conducted by Krif et al [80] reported that many PPNs populations were strongly correlated with soil clay, sand, and silt content in vegetable crops, while Van Diepeningen et al [81] demonstrated the same effect in both conventional and organic agricultural settings, and they found a prominent impact. In addition, this correlation could strongly define PPNs population structures [82,83].…”
Section: Discussionmentioning
confidence: 98%
“…The losses resulting from RKN infestation may be variable depending on the nematode species (Overstreet, 2009). Root-knot nematodes also cause necrosis and predispose the storage roots to cracking, which reduces their market value (Lawrence et al 1986). High population density of Helicotylenchus reduces the weight of tubers, roots, and shoot biomass (Lopez et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Morocco, such studies have revealed a greater diversity. There, 12 genera were found [15]. Root-knot nematodes of the genus Meloidogyne and the genus Tylenchorhynchus were detected in 100% of the sites surveyed.…”
Section: Discussionmentioning
confidence: 99%